Multiply Your Business Value Through Brand and AI. - Narayan, Rajan (New York : Business Expert Press, 2021)
This book presents the case for building brands effectively and optimally using AI, thereby enhancing the overall value of the organization. This book is ideal for entrepreneurs, investors, CEOs, and brand managers as it provides them with pathways of using AI to build brands and create value. It can be used as a textbook in courses on brand management and as a supplemental text in marketing management courses. It is especially relevant today, where many enterprises are being founded by non-marketing professionals.
Cover -- Halftitle -- Title -- Copyright -- Dedication -- Description -- Contents -- Preface -- Acknowledgments -- Chapter 1: Current Situation -- Chapter 2: Brand, a Guarantee of Value -- Chapter 3: An Introduction to AI -- Chapter 4: The Caveats of Using AI -- Chapter 5: Using AI to Identify and Get Insights About Customers -- Chapter 6: AI and Brand Development -- Chapter 7: AI and Creativity -- Chapter 8: AI in Customer Engagement -- Chapter 9: Improving the Customer's Brand Experience Using AI -- Chapter 10: The Balance Sheet -- Chapter 11: The Future Landscape -- Chapter 12: Starting the Process -- Bibliography -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Marketing; Branding (Marketing).; Artificial intelligence; Electronic books